Parks for aging: a toolkit for retrofitting parks to support the needs of older adults - Rader, Anna (Kansas State University, 2023)
The U.S. population is rapidly aging and diversifying (Vespa, Medina, and Armstrong 2020), and many older adults—those aged 65 and older—are choosing to age in their own homes and communities (Lehning, Smith, and Dunkle 2015). The concept of aging in one’s own community rather than in an institution is known as “aging in place” (CDC 2017). For aging in place to be possible, community infrastructure—such as parks and green spaces, public transit, or community centers—needs to be designed to be usable by older adults and enable them to age safely in their communities. Parks are an especially important age-friendly community infrastructure that provides many benefits to older adults (Kimic and Polko 2022) and can support their ability to age in place (WHO 2007). Although there are many studies that prove the benefits parks provide to older adults, there are few built parks designed specifically for the needs of older persons. In addition, most aging in place design guidelines focus on private residential modifications rather than adaptations to outdoor spaces within older adults’ communities. This study aims to address this gap by creating a Parks for Aging in Place Toolkit that helps facilitate age-friendly park retrofits. The Parks for Aging in Place Toolkit includes analytical tools and an assessment tool to help identify the needs of older parkgoers and assess the park’s current performance. The toolkit also provides design and activity programming recommendations for age-friendly park retrofits. Findings from a document analysis of universal design guidelines and precedent studies of activity programs informed the recommendations within the toolkit. Then, to illustrate its utility, the toolkit was applied to an existing park site: Franklin Park in Boston, MA. This park was selected as the application site due to the City of Boston’s eagerness to implement age-friendly public space design and the characteristics of the community surrounding the park. This study advances the research on age-friendly park design and provides landscape architects, parks and recreation professionals, design students, and community members with a tool to aid in initiating retrofits so that existing parks can better serve the needs of older adults. This project demonstrates that even simple design modifications in parks can improve older adults’ health and well-being, enabling them to age in place. The recommendations proposed in this project should benefit not only older adults but the greater population as well by increasing the usability and inclusiveness of park spaces. This project serves as a foundation for future age-friendly research and should inspire future age-friendly park retrofits.
Keywords: Aging; Parks; Landscape architecture; Retrofit; Older adults; Elderly